Pamflet şi satiră în publicistica românească (scurtă istorie a genului, din interbelic şi comunism până în anii 1990–2000) - Andrei Milca (Revista de Istorie și Teorie Literară)
In her book A pamphlet’s Anthology (from the Wallachian chroniclers to Pamfil Şeicaru), Magda Răduţă realizes a history of the representative articles of the most important romanian polemists writers and journalists – from the Enlightenment and Romanticism to the 20th Century – which used satire in their works. I analized the next period of time, the destiny of the pamphlet in the Romanian Communist Era (with a strong example: the nr. 1 polemist of the 1947–1989, Eugen Barbu) but also the proliferation of the Barbu’s „school”/tradition in the publishing of the 1990–2000 years, when the satire becomes, for many times, an attack to the person. In the inter-war years, we have redoubtable polemists, like Tudor Arghezi or N. D. Cocea; during the Communist Era: Eugen Barbu, Adrian Păunescu, Fănuş Neagu; after 1989 – Mircea Dinescu, Corneliu Vadim Tudor. The magazines where they published show the literary adversities/sides in the ’60–’70–’80 („Luceafărul”, „Săptămâna” vs „România literară”, Radio Free Europe) and in the 1990–2000 („România Mare”, „Totuşi iubirea” vs „Academia Caţavencu/Caţavencii”).